Nested-PCR based Detection of Hepatitis C Virus: Low-cost Strategy in Pakistan: Nested-PCR based detection of Hepatitis C virus - Rabia Javeed; Nabeela Tariq; Shakeela Daud; Asma Yousafzai; Saba Manzoor; Adeel Ahmad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
One of the most common blood-borne illnesses is hepatitis C virus (HCV), Hepatitis C is referred to as the inflammation of the liver and caused by the HCV virus, HCV is estimated to cause 53000 fatalities per year over the world. The majority of HCV-infected patients are unaware of their infection. No vaccine is available for HCV although Interferon is used to treat HCV but effective only 20-38 %, but at present, only a minority of infected persons have been tested and are aware of their diagnosis. The expense of testing may play a substantial role in patients' ability to get rid of the hepatitis C virus (HCV). Costs in many low- and middle-income nations, including Pakistan, force the development of novel and economically advantageous testing methods. The major aim of this study is about the effective diagnostic procedure for detecting Hepatitis C in the samples obtained from Balochistan, for this purpose the samples were collected from the health organization BINUQ (Balochistan Institute of Nephrology and Urology Quetta). Twenty (20) HCV antibodies positive patients in the Molecular Laboratory Department of Biotechnology were processed and then subjected to RNA extraction. cDNA was synthesized by reverse transcriptase enzyme. cDNA was used for qualitative analysis of HCV-RNA through nested PCR. According to the study, 09 samples were detected as positive and 7 samples were HCV negative out of 16 patients’ samples. The findings of the present study show comparison of the price for HCV- RNA tests per sample from patients with hepatitis C at various labs. When compared to the other five PCR-based tests in the laboratory-conducted anti-HCV, HCV qualitative, quantitative, and genotyping tests, Shoukat Khanum laboratory reported the most expensive costs for HCV -RNA tests. Dow laboratory HCV-RNA test is comparatively lower than Shoukat Khanum laboratory, while reported lowest and most cost-effective test of Molecular Diagnostic laboratory for anti-HCV. So, our molecular tests for HCV- RNA detection and quantitation showed very good diagnostic and clinical performance over all five public health laboratories.